Impact of probiotics on inflammatory bowel disease - a systematic review - Fijałkowska, Justyna; Pełka, Maciej; Kania, Anna; Ciulkiewicz, Łukasz (Journal of Education, Health and Sport, 2024)
Introduction: Inflammatory bowel disease (IBD) is a chronic nonspecific inflammatory disease of the gastrointestinal tract that includes ulcerative colitis (UC) and Crohn’s disease (CD). Both disease entities have many features in common, such as a basis of chronic inflammation, similar clinical symptoms as well as periods of remission and relapse. The difference between them lies in the lesions location. Treatment of IBD is primarily based on reducing inflammation and maintaining as long a remission time as possible. Increasing evidence is being attributed to the therapeutic potential of probiotics in IBD. Purpose: This review aims to present the preventive and therapeutic effects of probiotic use in IBS through an analysis of recent studies. Methods: A review of recent literature was conducted to investigate the impact of probiotic use on the treatment of IBD. Results: In studies, probiotics help induce and maintain remission in patients with mild to moderate ulcerative colitis, especially when used in combination therapy. In contrast, the usage of probiotics in Crohn’s disease does not provide due benefit: it does not induce or prolong remission. Conclusions: In conclusion, the effect of probiotics on IBD is inconclusive. Some probiotics, particularly the VSL#3 probiotic blend, have shown decent effects on induction and remission in patients with mild to moderate UC. However, no therapeutic effect has been demonstrated in patients with Crohn’s Disease. Therefore studies under more restrictive and standardized conditions are required.